PENGARUH PENILAIAN KINERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS PERIKANAN KABUPATEN WAJO SULAWESI SELATAN - Sofyan Marzuki (Universitas Mbojo Bima, 2023)
This study aims to determine the effect of performance appraisal on work productivity at the Fisheries Office of Wajo Regency, South Sulawesi. This research uses quantitative methods. Data collection techniques used were observation and questionnaires. The sample of this study were 43 people taken from a total population of 74 people. Data analysis in this study used correlation analysis, simple linear regression and anova test by conducting hypothesis testing. The results of this study were processed using the SPSS 26 application. The results of this study indicate that the Performance Assessment variable and the Work Productivity variable are each in the good category based on the respondents' responses. The results of other studies indicate that there is a relationship with the Fisheries Office of Wajo Regency, South Sulawesi.